2021
DOI: 10.1016/j.xjtc.2020.12.044
|View full text |Cite
|
Sign up to set email alerts
|

Aortic annuloplasty: Subcommissural, intra-annular suture techniques, external and internal rings

Abstract: Aortic valve repair and valve-preserving root replacement have evolved into increasingly practiced procedures. With increasing experience, the need for an annuloplasty has become more evident, at least for pathologies that involve annular dilatation. To understand the effect of an aortic annuloplasty, it is necessary to know the details of aortic valve and root anatomy. Geometrically, the functional annulus is best defined as the virtual basal ring, ie, plane of the cusp nadirs. The sinotubular diameter also i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(23 citation statements)
references
References 23 publications
0
23
0
Order By: Relevance
“…The accompanying review paper by Professor Scha¨fers' group nicely summarizes the concepts behind aortic valve annuloplasty. 1 The techniques include (1) subcommissural annular plication; (2) suture annuloplasty; (3) internal rings; (4) external rings or bands; and (5) reimplantation of the aortic valve. Of note, the first 3 options do not require deep circumferential dissection externally down to the basal ring.…”
Section: Are All Annuloplasty Techniques Equally Effective?mentioning
confidence: 99%
“…The accompanying review paper by Professor Scha¨fers' group nicely summarizes the concepts behind aortic valve annuloplasty. 1 The techniques include (1) subcommissural annular plication; (2) suture annuloplasty; (3) internal rings; (4) external rings or bands; and (5) reimplantation of the aortic valve. Of note, the first 3 options do not require deep circumferential dissection externally down to the basal ring.…”
Section: Are All Annuloplasty Techniques Equally Effective?mentioning
confidence: 99%
“…Although there are multiple subtle technical differences among the different publications in the literature, there are fundamental concepts, which when adhered to, allow for a more standardized approach and a more durable outcome than ever before. 3 , 4 , 5 , 6 In general, if there is adequate surface area and quality of valve leaflet tissue, and one uses precise preoperative imaging and intraoperative assessment and current reconstructive techniques, a competent/nonobstructive valve with very reasonable durability can be obtained. From a patient's perspective, the opportunity to retain one's own tissue, whose biologic behavior far exceeds that of any other biologic substitute at this time, will be much preferred if durability can be achieved.…”
mentioning
confidence: 99%
“…[1][2][3][4][5][6] The options for aortic annuloplasty have received considerable attention recently due to their importance for durability of aortic valve repair. 7,8 These annuloplasty options include a variety of suture techniques, as well as internal and external rings. [1][2][3][4][5][6][7] In this issue of the Journal, Tabrizi et al reported their clinical experience with an internal annuloplasty ring with ellipsoid geometry, with a focus on the perioperative and echocardiographic considerations.…”
mentioning
confidence: 99%